Application of Independent Curriculum in Improving Islamic Religious Education Learning - Ahmad Maulana Ashrafi; Hosna Rofiatul (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
This exploration examines the operation Independent Curriculum in improving the learning to education of religion students class V scholars at Integrated Islamic Elementary School Al- Adzkia Tembelang Jombang. This exploration uses a qualitative exploration approach with a descriptive qualitative exploration type. The data from this exploration uses 2 types of data, videlicet primary data and secondary data. The data collection fashion uses 3 styles, videlicet observation, interviews, and attestation class. The independent class is a new class launched by the Minister of Education and Culture, Nadiem Anwar Makarim, on February 11, 2022. The independent class is a literacy class that refers to an approach to scholars' bents and interests. This independent class was created with the end of perfecting education in Indonesia. The literacy process is the most important thing in education, where the commerce process between preceptors and scholars gets changed. The independent class helps in perfecting the literacy process of scholars because in this independent class, the literacy process is concentrated on the requirements of the scholars. At SDIT Al- Adzkia the literacy process by enforcing an independent class adapts to the requirements of scholars so that literacy is more meaningful and pleasurable. so that the literacy process can run well and scholars can admit literacy material more snappily.